Isaac Newton: Science and Religion in the Unity of his Thought - Henry, John (Estudios de Filosofía, 2008)
One of the main reasons for the success of Newton’s Natural Philosophy was the role that it played in the development of a valuable Natural Theology. Besides, Newton himself published the theological implications of his own Natural Philosophy. Although in the first edition of the Principia there is no sign of God, for the second edition (1713) Newton introduced a “General Scholium” in which he explicitly discussed the relation between God and His Creation. Newton`s obsession with the interpretation of Scriptures was for some time disregarded as awkward. Nonetheless, its importance for adequately understanding Newton is now accepted and it stimulates a lot of new activity on behalf of the specialists. This paper enables one to see at present the nucleus of the question posed by Richard H. Popkin: “Why one of the leading anti-Trinitarian theologians committed himself to writing works on Natural Philosophy, such as the Principia Mathematica?”